Rail Transit Development of the Pearl River Delta Planning, Obstacles and History - Bin Chen (Urban Rail Transit, 2018)
Abstract A new round of regional planning was conducted from 2014 to 2016 by the provincial government of Guangdong, providing an overview of the regional transportation development and history. Major problems in the Pearl River Delta (PRD) railway network are identified: the inconsistencies between railway planning and land use, lack of transit-oriented regional policy, issues regarding the competition and compatibility of different methods of transportation by rail. This paper incorporates the following solutions which include direct connection of major regional business centers,  improve railway and land use synergy, integrate railway and underground subway system and also discusses the future of railway transportation in densely populated areas.